Homeobox C9 suppresses Beclin1-mediated autophagy in glioblastoma by directly inhibiting the transcription of death-associated protein kinase 1. Issue 6 (17th November 2015) - Xuan, Fan; Huang, Mengying; Liu, Wen; Ding, Hanfei; Yang, Liqun; Cui, Hongjuan
Abstract: Background: The transcription factor homeobox C9 (HOXC9) plays a crucial role in developmental regulatory systems, where it determines the specific positional identities of cells along the anteroposterior axis. The expression of HOXC9 has been found to be dysregulated in some cancers such as lung cancer, breast cancer, and neuroblastoma. Here, we report for the first time that HOXC9 is a novel autophagy regulator and reveal its oncogenic role in cell survival and its usefulness as a prognostic marker in glioblastoma patients. Methods: Kaplan-Meier analysis was performed to evaluate the possible prognostic value of HOXC9 in glioblastoma. Growth curve assays, subcutaneous, and orthotopic implantations were used to analyze cell viability and tumor formation, respectively. Luciferase and chromatin immunoprecipitation assays were employed to explore the mechanisms involved in the association between HOXC9 and its downstream effector, death-associated protein kinase 1 (DAPK1). Results: High expression of HOXC9 was found to be an indicator of a poor prognosis in glioblastoma. HOXC9 knockdown resulted in a significant reduction of cell viability, migration, invasion, and tumorigenicity and a marked increase in autophagy. During the autophagy process, HOXC9 inhibited DAPK1 transcription by directly binding to its promoter. The downregulation of HOXC9 releases its transcriptional inhibition of DAPK1, resulting in the activation of the DAPK1-Beclin1 pathway, which induces autophagy in glioblastoma cells. Conclusions: Collectively, our data indicate that HOXC9 is an oncogene in glioblastoma. We have revealed its role in the control of autophagy, and we suggest that HOXC9 is a novel and promising therapeutic target.